Efferocytosis: a therapeutic strategy for diabetes and its vascular complications - Song, Yi; Yuan, Jiayi; Li, Yifan; Liu, Yifan; Qin, Guijun (Frontiers in Cell and Developmental Biology, 2025)
PurposeEfferocytosis is a continuous multistep process that efficiently clears dead cells and is essential for maintaining homeostasis in multicellular organisms. Under normal circumstances, apoptotic cells release “find-me” and “eat-me” signals that stimulate their engulfment and clearance. However, in many chronic inflammatory diseases, the clearance of apoptotic cells is significantly impaired. This review explores the relationship between defective efferocytosis and diabetes-related vascular complications, while investigating underlying pathophysiological mechanisms to identify novel therapeutic targets for disease management.MethodsAfter searching in PubMed and Web of Science databases using ‘efferocytosis’, ‘diabetic vascular complications’, and ‘efferocytosis-based therapy’ as keywords, studies related were compiled and examined.ResultsThis review summarizes the specific process of phagocytes engulfing and clearing dead cells, and explains the development of diabetes and its vascular complications from the perspective of defects in efferocytosis.ConclusionThe review points out that molecules and pathways associated with efferocytosis are potential targets for treating diabetic vascular complications, providing new ideas for clinical treatment.